MODERN PEDAGOGICAL TECHNOLOGIES IN THE ABSORPTION OF NATIONAL VALUES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article scientifically analyzes the significance and effectiveness of modern pedagogical technologies in instilling national values in the minds of the younger generation. In the context of globalization, where the preservation of national culture and spirituality has become a pressing issue, modern pedagogical approaches and innovative technologies serve as important tools for strengthening youth national identity, deeply understanding national values, and applying them in practice. The article thoroughly examines the role of technologies such as interactive learning, multimedia tools, virtual reality, gamification, and project-based learning in shaping national spiritual education, as well as their advantages and practical applications. The importance of teachers mastering modern technologies and applying them within the national context is also emphasized.